PAPAN SKOR VOLI BERBASIS MIKROKONTROLER DAN APLIKASI MOBILE - Rosidah; Silvia Syavira; Ocsirendi; Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
The scoreboard is an important component in volleyball matches for ease of recording scores. This final project creates an innovation for a microcontrollerbased scoreboard and mobile application. The system consists of two main components: a digital scoreboard controlled by a microcontroller and a wirelessly connected mobile application. A microcontroller is used to control the display of scores on a digital scoreboard, while a mobile application allows users to input and monitor scores in real-time. The wireless connection between the app and the scoreboard uses Wi-Fi technology, ensuring flexibility and mobility for users. Tests show that the combination of a microcontroller and a mobile application can increase efficiency and accuracy in managing volleyball match scores. Thus, the implementation of a microcontroller-based volleyball scoreboard and mobile application is expected to make a positive contribution in organizing volleyball matches.